If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 4y + 9y + 3x = 0 Reorder the terms: 6x + 3x + 4y + 9y = 0 Combine like terms: 6x + 3x = 9x 9x + 4y + 9y = 0 Combine like terms: 4y + 9y = 13y 9x + 13y = 0 Solving 9x + 13y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13y' to each side of the equation. 9x + 13y + -13y = 0 + -13y Combine like terms: 13y + -13y = 0 9x + 0 = 0 + -13y 9x = 0 + -13y Remove the zero: 9x = -13y Divide each side by '9'. x = -1.444444444y Simplifying x = -1.444444444y
| 12z+144=15(2) | | 12z+144=15*2 | | 15+5x=50 | | 38=19x | | 8(2n+3)=12 | | 4-9(5b-5)9(-7-6n)+35= | | (4x^2-x+5)=0 | | 6x^2=-3x | | 45x^2-49x+12.25=0 | | 20x^2=0 | | (x^2)+x-80=0 | | (x^2)+3x=240 | | 14m-3p+2m+6p=0 | | 7+9(-2n+9)+1= | | 4n-5n+3(n+4)= | | 2v^2+17v+35=0 | | -6(-6a-3)-2+8a= | | -5p+32=2(p-2) | | 4y-4=2-2(y-1) | | -a+7+5(-4+7a)= | | -6x-2(-5x+9)-3x= | | 3.1(2f+1.2)=0.2(f-6) | | 99-12t-(-7t)-4= | | -4(5+n)+n+6= | | 4m^2-20sm+25s^2=0 | | (4x^2-x+5)+(2x^2+x-7)=0 | | 9(3n-9)-7-2n= | | 42m=-906 | | m/25=13 | | 3z-6+8=23 | | -1+5a-9(-2+5a)= | | -2a+7-9(-2+5a)= |